Analysis Stability of Gabion Weir Design for Raw Water (A Case Study of Tidal Floods in Kawunganten Central Java) - Khamid, Abdul; Taufiq, Muhammad (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Global warming followed by climate change has become a new disaster in the world. One of the impacts of climate change that can be clearly seen is the rise of sea water to the land surface causing tidal floods in Cilacap Regency, Central Java Province. Research on Bronjong Dams as an appropriate alternative technology is the first step to overcome the problem of tidal flood mitigation and as a raw water filter. Research into planning the design of this Gabion Dam to handle tidal floods and as a filter to be used for raw water located at the mouth of the Parit River. The method used is a quantitative method by carrying out prototype testing to justify field conditions by handling close results. The research analysis technique begins with collecting primary data and secondary data.. The design of the Gabion weir models as a filter included three types of weir testing models namely type 1 trapezoidal model, type 2 beam model, and type 3 combination model. The material, geometry and dimensions of the experimental prototype are a reduction of the real problem conditions in the field. The results of the observation analysis of the Gabion weirs have obtained the average elevation of the water, MAR = 100 cm, MAB 600 cm, MAN = 450 cm, the elevation of the MAB upstream of the weir =650 cm, the elevation of the center of the weir = 445 cm, the downstream weir MAB = 410 cm, the measured flow velocity upstream of the weir 7.5 l/s, center 7.5 l/s, downstream 6.0 l/s and upstream temperature 31°C, center 30.3°C, 30°C, clean downstream water conditions. The results of the study represent a function of the elevation of the flood water level both upstream and downstream which are through the Gabion Weirs with several thicknesses as raw water filters